Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 476: 13



Work Step by Step

RECALL: $(f/g)(x)=\dfrac{f(x)}{g(x)}$ Thus, $(f/g)(x) = \dfrac{-2x+3}{x^2-5}$ To evaluate the given expression, substitute $-4$ to $x$ in the equation above to obtain: $f(-4)/g(-4) \\= (f/g)(-4) \\=\dfrac{-2(-4)+3}{(-4)^2-5} \\=\dfrac{8+3}{16-5} \\=\dfrac{11}{11} \\=1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.